Colorectal carcinoma masked by systemic inflammatory response syndrome: A case report - Wei, Hongyun (Oncol Lett, 2017)
The present study described the case of a 68-year-old woman who presented to the Second Xiangya Hospital of Central South University (Changsha, China) with progressive abdominal pain, distention and diarrhea. These symptoms were diagnosed as the initial manifestations of systemic inflammatory response syndrome associated with colorectal carcinoma (CRC). The presentation appeared as a common emergency medical case, which was eventually recognized as a CRC masked by this emergency symptom. This case highlights the fact that a correct diagnosis can be made by looking through the outward appearance to perceive the essence of the condition. Therefore, vigilant surveillance is of utmost importance in order to expedite prompt recognition and rapid management of this presentation of CRC.